Development of powtoon web apps assisted colloid system material animation video to increase students' interest in learning - Sabilla Wulan Sadewi; Agus Kamaludin (Pascasarjana Universitas Negeri Medan, 2023)
Colloidal material is theoretical and abstract, making it less attractive to students studying it. This study aims to develop an animated video for colloidal system material using the Powtoon web app and test its quality. This research method is Research and Development (R&D) using the ADDIE development model. Product assessment is carried out using product quality assessment sheets and student responses. Data analysis techniques use qualitative and quantitative analysis techniques described in descriptive form. The results of the evaluation of animated videos by material experts obtained an ideal percentage of 98.1% in the very good category, media experts 90% in the very good category, reviewers 94.8% in the very good variety, and students responded positively with a percentage of 93.4%. Based on the assessment results, it was concluded that the animated video developed could be used as an alternative learning medium in colloidal system material to increase students' interest in learning.Keywords: Animated video; Colloid system; Interest in learning; Powtoon